Estudo da influência dos óxidos de Mn, Co e Cr nas propriedades varistoras do sistema SnO2Nb2O5 - Bacelar Júnior, Wiss Kraw (Universidade Federal de São Carlos, 2000)
Aiming at obtaining SnO2 based varistor systems with a high degree of non linearity, new varistor compositions were studied, by means of doping the known SnO2.Nb2O5.CoO system with Cr2O3 and MnO2, as well as changing the CoO content. Processing parameters, such as sintering temperature, cooling rate, heat treatment atmosphere and composition, were analyzed, assessing therefore the specific role of dopants in the microstructural and electrical properties of a SnO2 varistor system and also optimizing the doping levels. The systems were sintered at different temperatures and cooling rates, aiming at obtaining better densification and electrical properties. X-ray diffractograms indicate the presence of a single phase. However the micrographs obtained by SEM showed the presence of phases segregated at the grain boundary region, and also revealed very porous surfaces, mainly in the systems presenting high manganese concentration. X-ray spectroscopy was used to anlyze the composition of these segregations, indicating the presence of "Mn, Co, Cr and O" in this region. I-V measurements were carried out and the best varistor response was from the system containing 1 mol% cobalt. The systems with higher manganese concentration presented smaller coefficients of non-linearity and also the addition of chromium oxide highly increased the tension of rupture. Analyses of the electrical measurements of the samples, carried out after heat treatment at oxydizing and reducing atmospheres suggest that the oxygen adsorbed at the grain boundary interface is the main source of charge carries, responsible by the non-linear behavior of the SnO2 based varistors.
Study of the influence of the oxides of Mn, Co and Cr in varistors properties SNO2.NB2O5 system
Keywords: Material cerâmico; Cerâmica eletrônica; Varistores; Estanho; Manganês; CIENCIAS EXATAS E DA TERRA::QUIMICA